Trust and cancer screening: Effects of a screening controversy on women’s perceptions of cervical cancer screening - B. O'Donovan; Therese Mooney; Ben Rimmer; Patricia Fitzpatrick; Grainne Flannelly; Lorraine Doherty; Noirin Russell; Cara M. Martin; John J. O'Leary; Linda Sharp; Mairead O'Connor (Preventive Medicine Reports, 2022)
There is a paucity of data on trust of service users in cervical screening. A significant controversy in Ireland’s national cervical cancer screening programme emerged in 2018. The Health Service Executive (HSE) confirmed that a clinical audit had revealed that more than 200 women who developed cancer had not been told of earlier misdiagnosed smear tests. During this high profile controversy we conducted qualitative interviews exploring factors that influence cervical screening participation. Women who had been invited for routine screening tests were recruited from the national screening register. Telephone interviews were conducted with 48 women aged 25–65 years; with a range of screening histories – 34 were adequately screened (attended all routine screening tests) and 14 were inadequately screened (attended some/no screening tests). Thematic analysis was conducted and all interviewees spontaneously raised the screening controversy revealing that the crisis had resulted in serious loss of trust, faith and confidence in the screening programme. Publicity surrounding the controversy had some beneficial effects, including increased awareness of the value of screening and beliefs that intense focus on the programme will improve the service long-term. Strategies which incorporate these findings could help rebuild trust in screening.